PERBANDINGAN PROPORSI SILICON TERHADAP HASIL JADI HAIR SHINE SPRAY - Diva Nur Aini; Megasari, Dindy Sinta; Wilujeng, Biyan Yesi; Faidah, Mutimmatul (Jurnal Tata Rias, 2026)
Hair shine spray is widely used as a styling product that relies on silicones for its shine effect. However, the proportion of silicones is crucial; too high can make hair feel heavy, while too low reduces product performance. This quantitative experimental study aimed to compare the effectiveness of silicone proportions in Formula 1 and Formula 2 on shine results, aroma, color, and preference level. Formula 1 used a different silicone proportion than Formula 2. Testing was conducted through an organoleptic test by 30 panelists and analyzed using the Independent Sample t-Test. Statistical results showed no significant difference between Formula 1 and Formula 2 in all tested aspects (p > 0.05). This suggests that the difference in silicone proportion did not yield a statistically significant effect on sensory quality. Nevertheless, descriptively, Formula 2 obtained a higher average score for all parameters, including shine (3.68) and preference level (3.71), compared to Formula 1. Thus, Formula 2 is superior in terms of consumer perception and preference.